Performance and emission characteristics of the thermal barrier coated SI engine by adding argon inert gas to intake mixture - T. Karthikeya Sharma (Journal of Advanced Research, 2015)
Dilution of the intake air of the SI engine with the inert gases is one of the emission control techniques like exhaust gas recirculation, water injection into combustion chamber and cyclic variability, without scarifying power output and/or thermal efficiency (TE). This paper investigates the effects of using argon (Ar) gas to mitigate the spark ignition engine intake air to enhance the performance and cut down the emissions mainly nitrogen oxides. The input variables of this study include the compression ratio, stroke length, and engine speed and argon concentration. Output parameters like TE, volumetric efficiency, heat release rates, brake power, exhaust gas temperature and emissions of NOx, CO2 and CO were studied in a thermal barrier coated SI engine, under variable argon concentrations. Results of this study showed that the inclusion of Argon to the input air of the thermal barrier coated SI engine has significantly improved the emission characteristics and engine’s performance within the range studied.